2010
DOI: 10.9755/ejfa.v22i5.4828
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chlorophyll mutants in Zingiber officinale Roscoe by Gamma Rays and EMS

Abstract: The present investigation comprises the data on frequency percentage of chlorophyll mutations in the different doses of gamma rays coupled with EMS in ginger. Different mutation frequencies and width of mutation spectra were induced under the action of different concentrations of the two applied mutagens. The spectrums of chlorophyll mutations (albino, xantha, and chlorina) were observed and grouped. The overall mutation spectrum for ginger showed that xantha occurred with the highest frequency, followed by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
3
10
0
1
Order By: Relevance
“…This might be due to the effect of EMS on M 0 seeds, which negatively affected the embryo, germination and this negative effect reflected on the plant growth and fruit formation of M 1 plants (including fruits and formed seeds inside the fruit), which in turn produced bad quality of seeds ( Abdul-Salam, 2007 ). In agreement with our results, previous studies found that the changes in the M 2 generation appeared during the seedling stage in the formation of chlorophyll or slow growth and also affected the growth until maturity ( Pawar et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…This might be due to the effect of EMS on M 0 seeds, which negatively affected the embryo, germination and this negative effect reflected on the plant growth and fruit formation of M 1 plants (including fruits and formed seeds inside the fruit), which in turn produced bad quality of seeds ( Abdul-Salam, 2007 ). In agreement with our results, previous studies found that the changes in the M 2 generation appeared during the seedling stage in the formation of chlorophyll or slow growth and also affected the growth until maturity ( Pawar et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…Ginger (Zingiber officinale Rosc.) is valuable plant all over the world as a spice in culinary preparations and for its medicinal properties (Jatoi et al, 2008;Pawar et al, 2010;Sivasothy et al, 2011). Ginger is native to India and South East Asia (Preeti et al, 2008;Abdullah et al, 2010;Tokuhara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the stronger mutagens reach their saturation point even at lower doses/concentrations in the highly mutable genotypes and further increase in dose/concentrations does not add to the mutation frequency. With an increase in dose/concentrations beyond a point, the strong mutagens become more toxic than the higher doses of relatively weaker mutagens.Higher frequencies of chlorophyll mutations with medium or lower doses of mutagens were reported by Srivastava et al, (1973) and Pawar et al, (2010) in different crops including chick pea.…”
Section: Discussionmentioning
confidence: 59%